Hospital-Acquired Pressure Injury: Risk-Adjusted Comparisons in an Integrated Healthcare Delivery System. Issue 1 (January 2018) - Rondinelli, June; Zuniga, Stephen; Kipnis, Patricia; Kawar, Lina Najib; Liu, Vincent; Escobar, Gabriel J.
Abstract : Background: Although healthcare organizations have decreased hospital-acquired pressure injury (HAPI) rates, HAPIs are not eliminated, driving further examination in both nursing and health services research. Objective: The objective was to describe HAPI incidence, risk factors, and risk-adjusted hospital variation within a California integrated healthcare system. Methods: Inpatient episodes were included in this retrospective cohort if patients were hospitalized between January 1, 2013, and June 30, 2015. The primary outcome was development of a HAPI over time. Predictors included cited HAPI risk factors in addition to incorporation of a longitudinal comorbidity burden (Comorbidity Point Score, Version 2 [COPS2]), a severity-of-illness score (Laboratory-Based Acute Physiology Score, Version 2 [LAPS2]), and the Braden Scale for Predicting Pressure Ulcer Risk. Results: Analyses included HAPI inpatient episodes ( n = 1661) and non-HAPI episodes ( n = 726, 605). HAPI incidence was 0.57 per 1, 000 patient days (95% CI [0.019, 3.805]) and 0.2% of episodes. A multivariate Cox proportional hazards model showed significant ( p < .001) hazard ratios (HRs) for the change from the 25th to the 75th percentile for age ( HR = 1.36, 95% CI [1.25, 1.45]), higher COPS2 scores ( HR = 1.10, 95% CI [1.04, 1.16]), and higher LAPS2 scores ( HR = 1.38, 95% CI [1.28, 1.50]). Female gender, an emergency room admission for a medical reason, and higher Braden scores showed significant protective HRs ( HR < 1.00, p < .001). After risk adjustment, significant variation remained among the 35 hospitals. Discussion: Results prompt the consideration of age, severity of illness (LAPS2), comorbidity indexes (COPS2), and the Braden score as important predictors for HAPI risk. HAPI rates may be low; however, because of significant individual site variation, HAPIs remain an area to explore through both research and quality improvement initiatives. Abstract : Supplemental digital content is available in the text.